Analisis Pengembangan Kapasitas Kelembagaan Pada Badan Kepegawaian, Pendidikan, dan Pelatihan Kota Semarang - Syifa Dwihastari; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Developing institutional capacity of local Government always contain an understanding of various efforts to improve service to the community. This research aims to find out and analyze developing institutional capacity in staffing agencies, education and training in Semarang. In addition, to know the driving factor and a barrier to developing institutional capacity in staffing agencies, education and training in Semarang. This research is descriptive using the type of qualitative approach. The results showed that lack of support from regulation, make the employees hardship to complete basic tasks and functions, especially in structuring the organization which has not been in accordance with the Government Regulations number 18 in 2016 about forming, and local regulations number 14 in 2016 on the establishment and composition of the regional city of Semarang can make the formation of the Officer has not been in accordance with duties and load. This factor is restricting institutional capacity building in the area of Staffing Agency in Semarang. Based on the results, it is recommended to the regional Staffing Agency in Semarang, associated with the regulations which are fluctuate, it is necessary to clarified about the rules that will be used, to avoid multiple interpretations of all parties, especially the regional Staffing Agency in Semarang.